The island - Paulsen, Gary. (New York : Dell, 1988)
Fifteen-year-old Wil discovers himself and the wonders of nature when he leaves home to live on an island in northern Wisconsin.
Junior High School Library Catalog (Wilson)
ALA Notable Books
Booklist
7.6
5-8
Keywords: Identity -- Fiction; Islands -- Fiction; Nature -- Fiction; Individuality -- Fiction; Islands -- Fiction; Nature -- Fiction; Wisconsin -- Fiction; Wisconsin -- Fiction